PENGARUH PARTISIPASI ANGGARAN, JOB RELEVANT INFORMATION DAN ASIMETRI INFORMASI PADA BUDGET SLACK - Prasetya, Ida Bagus Agung Adi; Muliartha RM, I Ketut (E-Jurnal Akuntansi; Vol 20 No 2 (2017)DO - 10.24843/EJA.2017.v20.i02.p25, 2017)
ABSTRACT The study was conducted in 3, 4 and 5 star hotels in Denpasar City due to the decrease in occupancy rate in hotel rooms while the number of tourists visiting Bali Province increased by 6.24% from the previous year. To achieve the purpose of this research is to use purposive sampling method with criteria of 12 star hotels 3, 4 and 5 in the city of Denpasar which has been operating for two years and the criteria of respondents amounted to 50 respondents who are all heads of departments who participate in budget making that has served at least one year. Data collection is done by distributing questionnaires directly to the hotel in Denpasar City. Analytical technique used is multiple linear regression as an analytical technique to get answers to research questions. The results of the analysis show that participation in budget making without supervision from superiors can open up opportunities for participating parties to budget slack with different asymmetry information from the principal and agent so that the information conveyed is different from the actual information, it can lead to slack On budget, the need for job relevant information in budget making so that managers can convey actual information in participating budget making and minimize the possibility of budget slack. This study concludes that budgetary participation and information asymmetry have a positive effect on budget slack and high job relevant information negatively affect budget slack. Keywords : i nformation asymmetry, job relevant information, budget slack, budget participation